(untitled) (Journal of Surgical Sciences, 2020)
Background: Acid burn injuries represent a special type of burn injury, with a pathophysiology depending on the type of acid, concentration, strength, quality, duration of contact, and penetration power. The consequence of acid attacks on survivors brings dramatic change in their lifestyle. The alarming increase of acid-throwing cases for the last 2 decades in Bangladesh is a cause of concern which led to its study. Objective: To describe the causes and consequences of acid violence among the acid burn victims in a specific center of Bangladesh. Methods: This is a cross sectional type of study conducted over a period of one year from December 2013 to November 2014 at Acid Survivors Foundation, Mirpur, Dhaka. 121 victims of acid violence were included in the study. Data collected by interviewing the patients using semi structured questionnaire which were later edited and analysed. Results: Among the respondents 25.6% (n= 31) were in the age group of 11 – 20 years, followed by 24.8% (n= 30) in the age group of 31 – 40 years. Causes of Threw Acid is 40.4% (49) cases were due to refusal of love or marriage proposal, in 27.3 (33) cases were due to dowry. Majority of cases affected on chest (62.0%), upper limb (58.7%), face (53.7%), neck (47.9%), back trunk (27.3%), lower limb (24.8%), abdomen (24.0%). Out of 121 patients 62.85% (n=44) needed single surgery, 28.57% (n=20) needed multiple setting surgery and 56.2% heal with minor scar, 25.6% had neck contracture, 21.5% had deformity in face. 81.0% are suffering from both anxiety and depression, 11.6% from anxiety alone and 7.4% from depression alone. Conclusion: A comprehensive effective, integrated, and gender specific medico-legal support for acid violence survivors should be ensured throughout the country. Journal of Surgical Sciences (2019) Vol. 23 (1) : 29-32